Phytochemical Investigation of Alkaloids in the Iraqi Echinops heterophyllus (Compositae) - Enas J. Khadim; Alaa A. Abdulrasool; Zainab J. Awad (College of Pharmacy University of Baghdad, 2017)
Alkaloids are a group of naturally occurring chemical compounds that contain mostly basic nitrogen atoms . They are a large family of compounds synthesized by plants in addition to the bacteria, fungi, and animals,  they often have pharmacological effects. The aim of this study is to isolate and identified alkaloids in a newly studied, wild Iraqi plant named Echinops heterophyllus. The medicinal importance of alkaloids, on one hand  and the absence of any phytochemical investigation on heterophyllus species of echinops genus on the other hand , acquired this study its importance. Three alkaloids (named E1, E2 and E3) were isolated from seed plant part by two chromatographic methods: Preparative high Performance Liquid Chromatography (PHPLC) and preparative thin layer chromatography (PTLC), one of them identified as(1-Methyl-2,3-dihydro-4(1H)-quinolinone by different chemical analysis like: ultra violet spectrum analysis (UV spectrum), Fourier transforms infrared spectra (FT-IR) , elemental microanalysis (CHN) and Proton1H-NMR and carbon 13C-NMR analysis. Key words: Echinops, heterophyllus, quinoline alkaloids.